PENDAMPINGAN PEMBUATAN GOOGLE MAPS BAGI PELAKU USAHA MIKRO KECIL MENENGAH MIE AYAM BELLEN DI DESA BUGIS - Nathisa Ismailiyya; Syifa Aprilyani Nurbaeti; Imron Fathurrohman; Septian Eka Prahardik; Nour Khalid (Jurnal Istimā, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are an essential sector in Indonesia’s economy, contributing to economic growth, job creation, and income distribution. However, many MSMEs are still unable to utilize digital technology, including Google Maps, as a promotional medium. One such example is the Mie Ayam Nok Bellen MSME in Bugis Village, which lacks knowledge of digital marketing, making its business location difficult for new customers to find. This community service activity aims to provide a strategic solution through assistance in creating a Google Maps business profile as a promotional tool and source of business information. Using a participatory approach, the community service team in Bugis Village was directly involved in the creation process, including completing business information, verifying the location, and uploading product and store photos. The results show that the MSME gained improved digital visibility, easier location access for customers, and expanded market potential. The impact of the assistance is reflected in the increased ease of customer navigation and the availability of more public information about the business, helping Mie Ayam Nok Bellen strengthen its competitiveness in the digital era.